Retinitis pigmentosa-associated cystoid macular oedema: pathogenesis and avenues of intervention. Issue 1 (2nd December 2016) - Strong, S; Liew, G; Michaelides, M
Abstract : Hereditary retinal diseases are now the leading cause of blindness certification in the working age population (age 16–64 years) in England and Wales, of which retinitis pigmentosa (RP) is the most common disorder. RP may be complicated by cystoid macular oedema (CMO), causing a reduction of central vision. The underlying pathogenesis of RP-associated CMO (RP-CMO) remains uncertain, however, several mechanisms have been proposed, including: (1) breakdown of the blood-retinal barrier, (2) failure (or dysfunction) of the pumping mechanism in the retinal pigment epithelial, (3) Müller cell oedema and dysfunction, (4) antiretinal antibodies and (5) vitreous traction. There are limited data on efficacy of treatments for RP-CMO. Treatments attempted to date include oral and topical carbonic anhydrase inhibitors, oral, topical, intravitreal and periocular steroids, topical non-steroidal anti-inflammatory medications, photocoagulation, vitrectomy with internal limiting membrane peel, oral lutein and intravitreal antivascular endothelial growth factor injections. This review summarises the evidence supporting these treatment modalities. Successful management of RP-CMO should aim to improve both quality and quantity of vision in the short term and may also slow central vision loss over time.